Mexican ceratopsids: considerations on their diversity and biogeography - Rivera-Sylva, Héctor E.; Frey, Eberhard; Stinnesbeck, Wolfgang (Journal of South American earth sciences, 2017)
During the past decade, three taxa of ceratopsid ornithischians have been described from Mexico. Apparently, this group experienced a regional diversification in this area. To date Mexican Ceratopsia are represented by three species, one of which is a centrosaurine and two are chasmosaurines. Here we provide a critical review on Mexican ceratopsians and formally name a new centrosaurine ceratopsid species from the Campanian Aguja Formation as Yehuecauhceratops mudei. We also discuss possible causes for the rapid endemic diversification of Mexican ceratopsians.